Less is More : Better Compliance and Increased Revenues by Streamlining Business Registration in Uganda - Sander, Cerstin (Washington, DC: World Bank, 2012)
A pilot of a streamlined business registration system in Entebbe, Uganda, reduced compliance costs for enterprises by 75 percent, raised registration numbers and fee revenue by 40 percent and reduced the cost of administering the system. It also reduced opportunities for corruption, improved relations between businesses and the local authorities and resulted in better compliance.